MODAL INTELEKTUAL DALAM PERBANKAN MENGGUNAKAN ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED - Kirana, Ardilla Ayu; Mahargiono, Pontjo Bambang (Jurnal Ilmiah Manajemen dan Bisnis (JIMBis), 2022)
The purpose of the study was to determine intellectual capital in banking using Economic Value Added (EVA) and Market Value Added (MVA) during the COVID-19 pandemic. Data was obtained using secondary and population data in this study using the banking sector listed on the IDX in 2019 to 2021. Data analysis used Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach using the WarpPLS application. The results showed that Value Added Capital Employed (VACA) had a positive and significant effect on Market Value Added (MVA), Value Added Human Capital (VAHU) had a positive and insignificant effect on Market Value Added (MVA), Structure Capital Value Added (STVA) positive and significant effect on Market Value Added (MVA), Value Added Capital Employed (VACA) positive and significant effect on Economic Value Added (EVA), Value Added Human Capital (VAHU) positive and significant effect on Economic Value Added (EVA), Structure Capital Value Added (STVA) has a positive and insignificant effect on Economic Value Added (EVA).